Resveratrol alleviates oxidative stress, inflammatory cytokine expression and apoptosis induced by nanoplastics in the hemocytes of abalone (Haliotis discus hannai) - Jiping Zhang; Qiyuan Fu; Yingjie Wang; Ye Mu; Hai Ren; Liyuan Xue; Jiahuan Liu (Aquaculture Reports)
The impact of nanoplastics (NPs) on molluskan hemocytes and the potential of resveratrol (RES) to counteract such effects require further investigation. The aim of the present study was to evaluate the effects of RES on oxidative stress, inflammatory cytokine expression and apoptosis induced by NPs in primary cultured hemocytes of abalone (Haliotis discus hannai). In this study, hemocytes of abalone were treated with control medium (control group), medium containing 100 μg/mL NPs (NPs group) or 100 μg/mL NPs + 1.14 μg/mL RES (NPs + RES group) in vitro for 24 h, respectively. Results showed that RES significantly restored the NPs-induced reduction in catalase and superoxide dismutase activity. Additionally, RES mitigated the increase of intracellular reactive oxygen species and malondialdehyde content induced by NPs. Relative mRNA expression of inflammatory genes (nf-κb, tnf-α, il-16 and il-17) and pro-apoptotic factor (caspase-3) were significantly up-regulated in the NPs group, while RES addition decreased the expression of these genes. RES also restored the NPs-induced reduction of antioxidant (nrf2, cat and cuznsod), anti-apoptotic (bcl-2) genes and SIRT1 protein expression. Meanwhile, the protein levels of ASC, cleaved caspase-3, IL-1β and nuclear translocation of NF-κB p65 induced by NPs was suppressed by RES addition. These results demonstrated that RES alleviated oxidative stress, inflammatory cytokine expression and apoptosis induced by NPs in abalone hemocytes. The Keap1/Nrf2, NF-κB and Bax/Bcl-2/caspase-3 signaling pathways were the main targets of the biological effects of RES in the presence of NPs.